OPTIMALISASI KETERBATASAN SARANA DAN PRASARANA SEKOLAH DALAM RANGKA MENINGKATKAN KUALITAS PEMBELAJARAN DI SD NEGERI 1 KEBON JERUK - Ria Nopitasari; Eliza Charlina; Jemi Adi Sastra; Muhammad Kaulan Karima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning in schools is inextricably linked to facilities and infrastructure. This article examines strategies for optimizing the limited facilities and infrastructure at SD Negeri 1 Kebon Jeruk to improve the quality of learning processes and outcomes. Facilities and infrastructure are fundamental to the implementation of effective learning in elementary schools. Limited facilities and infrastructure remain a major obstacle to the implementation of learning in many elementary schools. The management of facilities and infrastructure is a crucial aspect of school management to help achieve educational goals. The research method used was descriptive qualitative through literature review, non-participatory observation, and analysis of school documents. Optimizing facilities and infrastructure has been shown to have a positive impact on learning effectiveness and student engagement. Therefore, good management of facilities and infrastructure can help schools achieve educational goals even under limited conditions.